PENERAPAN MODEL PEMBELAJARAN TWO STAY TWO STRAY DALAM MENELAAH TEKS CERITA INSPIRATIF PADA PESERTA DIDIK KELAS IX SMP NU DARUL MA’ARIF KAPLONGAN KABUPATEN INDRAMAYU - Ade Hasanudin; Atang Supriatna (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The two stay two stray learning model was chosen by researchers because this model provides more time for students to discuss, so it is hoped that this model can help students in studying inspirational story texts. This research is experimental research. The population in this study were all class IX students at NU Darul Ma'arif Kaplongan Middle School, Indramayu Regency, totaling 211 students. The samples in this study were class IX B and class IX E. Learning test data studied inspirational story texts collected in the form of initial tests and final tests in the experimental class and control class. The research results obtained are as follows. First, the research test results can be seen in the Sig value. (2-tailed) is 0.000 < 0.05, then it is known that the t value is 6.328 > t table 2.004. Based on the above, H_0 is rejected and H_a is accepted, which means there is a difference in the average learning outcomes of students between the experimental class and the control class, in other words the application of the two stay two stray learning model in the experimental class and the direct learning model in the control class produce different learning outcomes. Second, based on the results of observations of learning activities using the two stay two stray model, it brings significant changes to learning activities in the classroom.